INDUCED REPRODUCTION OF Calophysus macropterus (Lichtenstein, 1819) WITH CARP PITUITARY EXTRACT IN MADRE DE DIOS REGION, PERU - BABILONIA-MEDINA, Jorge (2021)
The aim of this study was to evaluate a protocol for induced reproduction of Calophysus macropterus (Lichtenstein, 1819) in the Peruvian Amazon. Three females with maturing oocytes and three males that presented seminal fluid expulsion under light abdominal pressure were selected. The hormone inducer used was Carp Pituitary Extract (CPE) dissolved in physiological saline (0.9%), for females at 5.5 mg/kg and for males at 1 mg/kg, applied in two doses every 12 hours. Spawning was performed by stripping the abdomen of the females, the eggs were collected dry and immediately fertilized with the semen of the males. Incubation was carried out in 60 L capacity Woynarovich type cylindrical conical upflow incubators. The results showed spawning of two females at 168,16 and 187,5 degree-hours (27,3 and 27.5 °C), with post hormone induction latency time of 6,16 and 6,82 hours. Hatching of larvae was only achieved from the first female, which occurred at 15,3 h post-incubation (28,2 °C) with a total of 300 larvae, however at 3 days there was mortality of all individuals. The preliminary results of this study provide knowledge on the induced reproduction of C. macropterus as a basis for the production of this species in aquaculture systems in the Peruvian Amazon.